Assessing the interrelationship between stigma, social influence, and cervical cancer prevention in an urban underserved setting: An exploratory study. - Caryn E Peterson; J Andrew Dykens; Stevan M Weine; Hunter K Holt; Judes Fleurimont; Christina G Hutten; John Wieser; Fida Abuisneineh; Saria Awadalla; Natalia P Ongtengco; Nicole Gastala; Ian G Jasenof (PLoS ONE, 2022)
In the US, incidence and mortality from cervical cancer disproportionately affects racial/ethnic minorities and low-income women. Despite affordable access to primary and secondary prevention measures at Federally Qualified Health Centers (FQHCs), Human Papillomavirus (HPV) vaccination and screening rates are low, suggesting the presence of non-financial barriers to uptake in this population. This explanatory sequential mixed-methods study sought to explore factors that influence the acceptability of cervical cancer prevention services among parents and legal guardians of vaccine-eligible girls attending an urban FQHC and to assess social influences related to cervical cancer prevention. Participants included eight mothers, one father, and two grandparents/legal guardians. Nine participants self-identified as Black/Afro-Caribbean, or African American, two as Latinx, and one as Native American. The quantitative data suggested discordance between participants' cervical cancer prevention knowledge and their practices. Most indicated that their daughters had received the HPV vaccine but were unsure about HPV transmission modes. Qualitative data revealed that participants were comfortable disclosing information on HPV infection and vaccination status, and most women were likely to share information related to cervical cancer testing and diagnosis. Few comments indicated personal stigma on the part of participants, but there was frequent expression of perceived public stigma (shaming and blaming women), gender differences (men are indifferent to risk), and distrust of the healthcare system. Findings highlight several concepts including the disharmony between knowledge and practice, prevalent perceived public stigma, cumbersome attitudes on the part of men regarding HPV and cervical cancer, and distrust of the healthcare system.